Race and ethnic relations 09/10 - Kromkowski, John A. (Annual editions, 2010)
Provides an access to a wide range of articles from some of the magazines, newspapers, and journals published. This title provides a number of common organizational features: a general introduction; an annotated table of contents; a topic guide; an annotated listing of selected World Wide Web sites; and a brief overview for each section.